Trochanteric fracture following hip arthrodesis: case presentation. Issue 1 (7th December 2017) - Deleanu, Bogdan; Prejbeanu, Radu; Vermesan, Dinu; Haragus, Horia; Honcea, Lucian; Mioc, Mihail‐Lazar; Tsiridis, Eleftherios; Predescu, Vlad
Key Clinical Message: Even if the intertrochanteric fracture under an arthrodesis hip is rare and the optimal surgical treatment is controversial, we consider that treating this kind of fracture with a locked plate was a success. Abstract : Even if the intertrochanteric fracture under an arthrodesis hip is rare and the optimal surgical treatment is controversial, we consider that treating this kind of fracture with a locked plate was a success.